Genotype-environment interaction and guata potato yield (Solanum tuberosum L.) in the Department of Nariño (Colombia) (2021)
Estimating the genotype-environment interaction (GEI) for potato genotype yield is very useful for the identification of outstanding genetic material that can adapt to specific environmental conditions and shows productive potential for breeding programs, selection processes and cultivar recommendations because it improves the efficiency of the genetic improvement process. The objective of this study was to determine the GEI of yield, expressed as t ha-1, in 21 potato genotypes. Four municipalities in the Department of Nariño were considered: Tangua, Pupiales, Imues, and Pasto. A randomized complete block design and an additive main effects and multiplicative interaction model (AMMI model) were used. Highly significant differences between the environments were found across the genotypes and GEI. Of the total variation, 42.43% was explained by the environment, 13.84% by the genotypes, and 15.49% by the GEI. The genotypes that showed stable behaviors were UdenarStGua55, UdenarStGua78, UdenarStGua24, UdenarStGua61, UdenarStGua20, and UdenarStGua98. Genotypes UdenarStGua78 and UdenarStGua98 stood out with 53.49 and 48.42 t ha-1 . Furthermore, genotypes UdenarStGua93, UdenarStGua97, and UdenarStGua91 showed a positive interaction with the environments of Tangua and Pupiales. Similarly, genotypes UdenarStGua58, UdenarStGua83, UdenarStGua57, and UdenarStGua87 positively interacted with Pasto, while genotypes UdenarStGua78 and UdenarStGua98 showed positive interactions with Imues. The genotypes displayed different behaviors in response to the areas where they were established, which varied in altitude, soil type, and environmental conditions.